More control–less agency slack? Principal control and the risk of agency slack in international organizations - Vytautas Jankauskas; Christoph Knill; Louisa Bayerlein (Regulation & Governance, 2023)
Principal-agent theorizing is based on the idea of a linear inverse relationship between principal control and agency slack: the higher the control over the agent, the less likely is the agent to slack. In this paper, we challenge this assumption by explicitly taking the varying nature of agents into account. While control may reduce the agent's room for maneuver, it does not explain the extent to which different agents are inclined to put efforts in circumventing these obstacles. Focusing on international organizations (IOs), we measure member states' as principals' control over IO administrations as their agents as well as the latter's intrinsic propensity to slack across eight major IOs. The analysis shows that low control by the principal is not necessarily associated with run-away agents, whereas high control is not necessarily associated with servant-like agents. The assumed control–slack relationship can thus be distorted and determining an ideal level of control is not possible without considering the agent's entrepreneurialism.
Keywords: 330; agency slack; control; international organization; international public administration; principal-agent theory